2010
DOI: 10.1007/s10517-010-1095-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Myogenic Reaction and Autoregulation of Cerebral Circulation

Abstract: Dilatation of rat pial arterioles at constant arteriolar wall strain during autoregulation of cerebral circulation was shown by the method of biomicroscopy. Wavelet-analysis of cerebral blood flow oscillations during this period revealed increased oscillation amplitude in the endothelial and neurogenic frequency ranges and unchanged amplitude at myogenic frequency range. These findings probably attest to the leading role of myogenic reaction in the autoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The studies with animal cohorts utilized various animals, including albino mature outbred male rats [ 99 ], Wistar male rats [ 101 ], female hooded lister rats [ 102 ], and, in one instance, goats [ 100 ]. The studies measured either CBF with a laser Doppler flowmetry [ 99 , 102 ] or an electromagnetic flow probe [ 100 ], or CBFv using a TCD probe [ 101 ]. All studies carried out modeling tasks and reported an effective modeling of CBFv or CBF signals to assess CA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies with animal cohorts utilized various animals, including albino mature outbred male rats [ 99 ], Wistar male rats [ 101 ], female hooded lister rats [ 102 ], and, in one instance, goats [ 100 ]. The studies measured either CBF with a laser Doppler flowmetry [ 99 , 102 ] or an electromagnetic flow probe [ 100 ], or CBFv using a TCD probe [ 101 ]. All studies carried out modeling tasks and reported an effective modeling of CBFv or CBF signals to assess CA.…”
Section: Resultsmentioning
confidence: 99%
“…Wavelet analysis was employed by Alexandrin to study the myogenic response of pial arteries [ 99 ]. Doblar et al employed Fourier analysis to examine the effects of hypoxia on the dynamic characteristics of cerebrovascular responses [ 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main aim was to test the arteriolar responses to the following substances able to dilate or inhibit the dilation of vessels: acetylcholine (Ach), known to facilitate endothelium-dependent arteriolar dilation; Nω-nitro- L -arginine ( L -NNA), inhibitor of eNOS; indomethacin (INDO), inhibitor of prostaglandin endoperoxidase; and charybdotoxin plus apamin, inhibitors of EDHF [15]. Previous studies have indicated that dilation of pial vessels is resistant to inhibitors of NO synthase and cyclooxygenase, suggesting a role for a third endothelium-dependent mechanism in cerebral vessel tone modulation and blood flow distribution [16,17,18,19,20,21]. Consequently, we tested arteriolar responses to papaverine (Pap), known as an NO-independent vasodilator.…”
Section: Introductionmentioning
confidence: 99%